Multiply Charged Helium Droplet Anions. Issue 25 (12th March 2021) - Laimer, Felix; Zappa, Fabio; Scheier, Paul; Gatchell, Michael
Abstract: The detection of multiply charged helium droplet anions is reported for the first time. By ionizing droplets of superfluid helium with low energy electrons (up to 25 eV), it was possible to produce droplets containing up to five negative charges, which remain intact on the timescale of the experiment. The appearance sizes for different charge states are determined and are found to be orders of magnitude larger than for the equivalent cationic droplets, starting at 4 million He atoms for dianions. Droplets with He* − as charge carriers show signs of being metastable, but this effect is quenched by the pickup of water molecules. Abstract : Charged droplets : The detection of multiply charged helium droplet anions is reported for the first time. By ionizing droplets of superfluid helium with low energy electrons (up to 25 eV), it was possible to produce droplets containing up to five negative charges, which remain intact on the timescale of the experiment.